2012
DOI: 10.1115/1.4007429
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Laminar Slip-Flow Thermal Transport in Microchannels With Transverse Rib and Cavity Structured Superhydrophobic Walls at Constant Heat Flux

Abstract: This paper presents an analytical investigation of the thermal transport in a parallel-plate channel comprised of superhydrophobic walls. An analytical solution is obtained for the thermally developing state, however, it is the condition far downstream from the entrance where the temperature field exhibits repeating periodic streamwise variation that is of primary interest here. The superhydrophobic walls considered in this paper exhibit alternating microribs and cavities positioned perpendicular to the flow d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…10 are results at ^" = 0.1 from Ref. [30] where the transverse rib scenario was explored. For this scenario, the influence of axial conduction was neglected.…”
Section: Average Nusselt Number Behaviormentioning
confidence: 98%
See 2 more Smart Citations
“…10 are results at ^" = 0.1 from Ref. [30] where the transverse rib scenario was explored. For this scenario, the influence of axial conduction was neglected.…”
Section: Average Nusselt Number Behaviormentioning
confidence: 98%
“…However, in this study, periodicity of the heating was neglected although it is a critical feature of the thermal transport dynamics. Two studies by our group have explored heat transfer in laminar duct fiows with SH walls exhibiting transverse ribs maintained at constant temperature [23] and at constant heat flux [30]. The results from these works showed that the average convective heat transfer coefficient, h, is smaller for SH surfaces than for the non-SH surfaces.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…2), with ridge height d, with air (of thermal conductivity k a = 0.028 W/mK) filling the interstices between the ridges, and assuming a flat air meniscus. 18,22 A linear air fraction was defined through φ a = l a /L (where l a is the width of the air pocket and L is the combined width of the solid rib of length l s and the air pocket, i.e., L = l s + l a ). The substrate is of thickness D and thermal conductivity k s .…”
Section: Methodsmentioning
confidence: 99%
“…Distinct results are expected for systems concerning effective slip (Maynes, Webb & Davies 2008;Maynes et al 2012;Enright et al 2013). As such, the Graetz-Nusselt problem for heterogeneously slippery surfaces deserves to be studied separately.…”
Section: On Nu ∞ and Its Transition Pointmentioning
confidence: 99%